Public Administration and Municipal Governance and Its Significance for a Modern Democratic Society - Buley, Natal’ya V.; Bondaletov, Valery V.; Makushkin, Sergey A.; Bondaletova, Natalia F.; Kozyrev, Maxim S. (International Journal of Economics and Financial Issues, 2016)
This paper aims to review the state of public administration and municipal governance today. The condition of state and municipal administration is considered on the example of modern democratic society. As the highest type of administration activities, social management is the effect of the subject on the public relations with the purpose of their improvement, development and streamlining, preservation of their qualitative specificity. The main feature of social control is that the object is the activities the subjects of knowledge. That is, the subjects of knowledge, and the real actors are the people themselves. In addition, the interaction between subject and object of knowledge is the object of knowledge. Management “is the property of any society arising from its systemic nature, the public nature of labor, the need of communication between people in work and life, the exchange of products, their material and spiritual activities.” Depending on the nature of the subject of management, there is control of the state (subject of control - state) and municipal administration (the subject of administration - the population of the municipality). Keywords: public administration, municipal governance, democratic society, economic growth, economic development JEL Classifications: H1, H11, H7, H75